Intangible Assets and Performance in Nonprofit Organizations:A Systematic Literature Review - Buonomo, Ilaria; Benevene, Paula; Barbieri, Barbara; Cortini, Michela (Frontiers in Psychology, 2020)
Nonprofit organizations (NPOs) promote citizens’ participation in community life through several different kinds of organizations: some more informal (such as associations and volunteering groups), others more formal or public (such as charities and foundations). This heterogeneity, as well as the well-known peculiarities of nonprofit organizations when compared to profit and public ones, poses new challenges to their management. In the constant need to find balance between financial constraints and social value, a main resource for NPOs is the management of intangible assets, such as knowledge, positive relationships within the organization and with users, external image, loyalty and commitment, and so on. From the literature on for-profit organizations, it is well known that proper management of intangible assets improves an organization’s sustainable competitive advantage, not only by enhancing its members’ affiliation and commitment but even by enhancing their productivity. This is particularly relevant when taking into account the main role of volunteers in the third sector. Volunteers, indeed, show different job attitudes and organizational behaviors than paid employees, as their membership and accountability are less formalized and they frequently lack a proper teamwork, due to the high volunteer turnover. At the same time, from the managers point of view, managing volunteers and paid workers require higher skills and competencies than managing human resources in for-profit organizations. Developing these reflections and considerations, we aim to conduct a systematic literature review on the association between intangible assets and performance in nonprofit organizations. The literature will be conducted following the indications from the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. It provides an evidence-based minimum set of items to be included in the review, as well as a workflow to properly manage and choose the papers to be included. The authors conducted the research using EBSCO, ProQuest and Scopus databases.